2004
DOI: 10.1093/nar/gnh030
|View full text |Cite
|
Sign up to set email alerts
|

Shuffled antibody libraries created by in vivo homologous recombination and yeast surface display

Abstract: Homologous recombination in yeast can be exploited to reliably generate libraries of >10(7) transformants from a pool of PCR products and a linearized plasmid vector. Homology in the PCR insertion products drives shuffling of these genes in vivo by yeast homologous recombination. Two scFvs that share 89.8% homology were shuffled in vivo by homologous recombination, and chimeric genes were generated regardless of whether or not one of the scFv PCR products lacked 5' homology to the cut vector and the second scF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 24 publications
1
55
0
Order By: Relevance
“…These techniques are attractive for their simplicity, as they require only a straightforward transformation step. In vivo homologous recombination has also been used extensively in the context of library generation for directed evolution applications; the highly efficient recombination machinery of organisms such as Saccharomyces cerevisiae has frequently been employed to build single-gene libraries containing 10 4 -10 10 variants (22)(23)(24)(25)(26). However, previously reported in vivo assembly techniques for multigene constructs have been low yielding, generating only tens to hundreds of recombinants at a time and making them impractical for the construction of libraries.…”
mentioning
confidence: 99%
“…These techniques are attractive for their simplicity, as they require only a straightforward transformation step. In vivo homologous recombination has also been used extensively in the context of library generation for directed evolution applications; the highly efficient recombination machinery of organisms such as Saccharomyces cerevisiae has frequently been employed to build single-gene libraries containing 10 4 -10 10 variants (22)(23)(24)(25)(26). However, previously reported in vivo assembly techniques for multigene constructs have been low yielding, generating only tens to hundreds of recombinants at a time and making them impractical for the construction of libraries.…”
mentioning
confidence: 99%
“…For the insertion of a (G 4 S) 3 linker between VH and VL gene, the following sequence was added to the 5 0 end of the VH reverse primer (5 0 -CGA GCC CCC GCC ACC CGA ACC GCC CCC ACC TCT-3 0 ) and the 5 0 end of the V j and V k forward primer (5 0 -GGT TCG GGT GGC GGG GGC TCG GGC GGG GGT GGC TCA GAT CT-3 0 ). To allow homologous recombination of amplified scFv inserts with pCTCON by gap repair function [15], the following sequence was added to the 5 0 end of the VH forward primer (5 0 -AGT GGT GGT GGT GGT TCT GGT GGT GGT GGT TCT GGT GGT GGT GGT TCT GCT AGC-3 0 ) and the 5 0 end of the V j and V k reverse primer (5 0 -TCA GAT CTC GAG CTA TTA CAA GTC CTC TTC AGA AAT AAG CTT TTG TTC GGA TCC-3 0 ). Then each amplified VH and VL family gene was purified from 1% agarose gels and quantified by absorbance at 260 nM.…”
Section: Methodsmentioning
confidence: 99%
“…The assembled scFv gene products ($800-850 bp) were purified from 1% agarose gels and concentrated using Pellet Paintä (Novagen) [12]. The scFv antibody gene libraries (10 lg) were mixed with linearized pCTCON (1 lg) by NheI/BamHI digestion, and were transformed into the yeast EBY100 strain by homologous recombination using a Bio-Rad Gene Pulser electroporation apparatus [12,15]. A total of four transformations were performed in parallel.…”
Section: Methodsmentioning
confidence: 99%
“…Although in vivo homeologous recombination has been described in wild type cells, [29][30][31][32] there seem to be a limit in the number and size of fragments and their nucleotide divergence preventing the correct recombination of non-identical sequences in DNA repair proficient cells. It was reported that double and single strands breaks license chromatid exchanges.…”
Section: From Mosaic Genes To Intragenic Mosaic Pathwaysmentioning
confidence: 99%